Acceleration of granulation tissue using myrmecodiapendens extract induction during wound healing tooth extraction process (experimental research on caviacobaya) - Efa Ismardianita; Wenny Rosalina (Journal of Dentomaxillofacial Science, 2020)
Objective:To identify the effect of myrmecodiapendens extract 20% on granulation tissue post-tooth extraction.Material and Methods: Twenty-four caviacobaya divided into two groups: the control group and treatment group. Lower left incisor tooth subjects were extracted and the entire socket filled with CMC 0.5% in the control group and myrmecodiapendens extract 20% in the treatment group, 0.1 CC in each subject. On days 3, 7, 14, and 21 subjects were determined, subsequently, socket tissues were stained with Haematoxylin Eosin (HE) technique. Angiogenesis, fibroblast, and macrophage were used to evaluatedÂ granulation tissue on wound healing post-tooth extraction. Data were analyzed with the Kruskal-Wallis test to see differences between the control group and treatment group with a level of significant p <0.05.Results: This study indicates significant differences in angiogenesis, fibroblast, and macrophage between control group and treatment group (p <0.05).Conclusion: This study confirmed the effect of myrmecodiapendens extract 20% increase angiogenesis, fibroblast, and macrophage, which is can improve wound healing process post-tooth extraction.